Answer :

Answer:

Q = (- 3, 5 )

Step-by-step explanation:

Given the 2 equations

3y - 2x = 21 → (1)

4y + 5x = 5 → (2)

Multiplying (1) by 5 and (2) by 2 and adding will eliminate the x- term.

15y - 10x = 105 → (3)

8y + 10x = 10 → (4)

Add (3) and (4) term by term to eliminate x

23y = 115 ( divide both sides by 23 )

y = 5

Substitute y = 5 into either of the 2 equations and solve for x

Substituting into (2)

4(5) + 5x = 5

20 + 5x = 5 ( subtract 20 from both sides )

5x = - 15 ( divide both sides by 5 )

x = - 3

Solution is (- 3, 5 )

Other Questions